Homelies sette fourth by the righte reuerende father in God, Edmunde Bishop of London not onely promised before in his booke, intituled, A necessary doctrine, but also now of late adioyned, and added therevnto, to be reade within his diocesse of London, of all persons, vycars, and curates, vnto their parishioners, vpon sondayes, & holydaies - Bonner, Edmund 1500?-1569 (Early English Books Online / EEBO, 1555)
eebo-0014